The Relationship between Stress Coping and Cadets’ Learning Motivation in Vocational Maritime Education and Policy Formulation - Purwiyanto, Didik; Purwanto, A; Setiono , B A; Sudirman, Sudirman (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2025)
This study aims to analyze the relationship between stress coping and cadets’ learning motivation in Vocational Maritime Education and to formulate relevant policies. The study population consisted of 95 first-year cadets’ at the Vocational Faculty of Maritime. The sampling technique used was saturated sampling, where all 95 cadets’ became research participants. Data collection methods included questionnaires, observations, and interviews. Data analysis was conducted using multiple regression analysis, with hypothesis testing performed using t-tests and F-tests. The results showed that Emotion-Focused Coping did not significantly affect learning motivation when analyzed separately. However, Problem-Focused Coping had a significant impact on learning motivation. When considered simultaneously, both coping strategies significantly influenced cadets’' learning motivation. Based on these findings, this study suggests the necessity of a comprehensive policy to help cadets’ manage stress. This includes providing guidance and counseling services and developing effective stress management training programs to enhance cadets’ well-being, reduce dropout rates, and increase learning motivation. Implementing these policies is expected to support cadets’ in achieving optimal academic performance and completing their education on time.